PEMBUKTIAN DUA PULUH LIMA DALIL PYTHAGORAS - Sunaryo, Sunaryo; Sunardi, Hartanto (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2015)
Mathematics is a discipline that can help Pythagoras solve some various problems (Government,Industry, science) Pythagoras is the first person who contributed the proof of this theorem, however, many people believe that there is a special connection between the sides of a ringt triangle just a long before Phytagoras found it. However Phytagoras gave very significant important role in various major related to mathematics. For example to form trigonometri and algebra, this theorem is a connection between Euclidean geometry among the three sides of the triangle which shaped from the length of the two sides will equalto square number which formed by the hypotenuse. In athematics, Phytagoras theorem is written using the general form , where a and b represent the length of two other condition of a right triagle and c has a length of the hypotenuse. This observation aim to describe there verification of twenty five arguments of Phytagoras appropriately and correctly. And by knowing the expected arguments of Phytagoras makes learning math is not just memorize a formula but to understand more deeply and can be implemented in their daily lives. This research method using the method of literature from the literature study theore hcal framework underlying stuctored problem soling method that includes the use of the arguments of Phytagras, Phytagoras formula, triple Phytagoras, comparison of the sides of aright triangle for special angels and lines o the trigle. Keywords : Phytagoras, hipotenusa.